Successful treatment of hemochromatosis with renal tubular dysgenesis in a preterm infant. Issue 8 (20th June 2015) - Koura, Uta; Horikawa, Shinjiro; Okabe, Mako; Kawasaki, Yukako; Makimoto, Masami; Mizuta, Koichi; Yoshida, Taketoshi
Key Clinical Message: We report the first surviving case of neonatal hemochromatosis with renal tubular dysgenesis. Renal failure was treated with peritoneal dialysis. Although hepatic failure from neonatal hemochromatosis was progressive, repeated exchange transfusions improved jaundice and coagulopathy. The patient gained weight and received a liver transplantation from her father. Abstract : We report the first surviving case of neonatal hemochromatosis with renal tubular dysgenesis. Renal failure was treated with peritoneal dialysis. Although hepatic failure from neonatal hemochromatosis was progressive, repeated exchange transfusions improved jaundice and coagulopathy. The patient gained weight and received a liver transplantation from her father.